Komunikasi Ritual Kanuri Blang sebagai Bentuk Kebersamaan Masyarakat Tani Kecamatan Samatiga Kabupaten Aceh Barat Propinsi Aceh - K.S. Maifianti; S. Sarwoprasodjo; D. Susanto (Institut Pertanian Bogor, 2014)
AbstractKanuri blang an customs tradition of of farmer communities in Aceh for generations that may indirectly improve the production of rice. The purpose of this study is to look at the communication rituals that occur in Kanuri blang among the farming community. The benefit is expected to help the instructor so that utilizes Kanuri blang as a place to inform the things that are important to farmers. To obtain maximum results with the study researchers used a qualitative approach and using ethnographic methods of communication. Where data collection using direct observation, in-depth interviews and focus group discussions (FGDs). Blang Kanuri is a place to gather, share, and participate together farming community. Kanuri blang conducted on an annual entry of the growing season to be exact month of Muharram.Keyword: kanuri blang, ritual communication, solidarity